2009
DOI: 10.1002/anie.200901410
|View full text |Cite
|
Sign up to set email alerts
|

The Benzyne Aza‐Claisen Reaction

Abstract: Adding an aryne to a tertiary allylamine affords o-allylaniline products of an aza-Claisen rearrangement. The aryne simultaneously provides the pi component for the rearrangement and the quaternization event that lowers the activation energy for the sigmatropic shift. The reaction was applied to the synthesis of medium-ring benzannulated amines (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 57 publications
3
60
0
Order By: Relevance
“…[13] Medium-sized (8-to 10-membered), nitrogen-containing heterocycles are very difficult to synthesize, but their biological importance motivated us to apply this reaction to the synthesis of 9-and 10-membered cyclic heterocycles. Previously reported syntheses of medium-sized, nitrogen-containing heterocycles that use aryne intermediates include the aza-Claisen rearrangement of cyclic allylamines, [14] the benzyne-mediated ring expansion of 2-vinylazetidines, [15] and the C-N single-bond insertion reaction of cyclic urea derivatives. [16] Although these methods are synthetically valuable, the substrate scope is very limited owing to the low availability of the starting amines.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Medium-sized (8-to 10-membered), nitrogen-containing heterocycles are very difficult to synthesize, but their biological importance motivated us to apply this reaction to the synthesis of 9-and 10-membered cyclic heterocycles. Previously reported syntheses of medium-sized, nitrogen-containing heterocycles that use aryne intermediates include the aza-Claisen rearrangement of cyclic allylamines, [14] the benzyne-mediated ring expansion of 2-vinylazetidines, [15] and the C-N single-bond insertion reaction of cyclic urea derivatives. [16] Although these methods are synthetically valuable, the substrate scope is very limited owing to the low availability of the starting amines.…”
Section: Resultsmentioning
confidence: 99%
“…A nitrogen atom of trifluoromethanesulfinamides (N-S bond) 145 and aminosilanes (N-Si bond) 103 also serves as the nucleophilic site for the aryne insertion reaction (Scheme 37), and furthermore a formal insertion into a N-C(allyl) bond of tertiary allylamines proceeds through initial formation of ammonium salt 35 and subsequent charge-accelerated aza-Claizen rearrangement (Scheme 38, path A). 106 In this reaction, 6-endo S N 2 0 reaction of zwitterion 36 is not operative (path B). nucleophilic addition of the C-C triple bond (not the oxygen atom), which is totally different from the routine mechanism (Scheme 41).…”
Section: 2 Addition Of R-bondsmentioning
confidence: 97%
“…54 Because a cumulenic resonance structure of 2,3-pyridyne 27 exerts significant effect on the regioselectivity, the nucleophilic coupling at the ortho-position takes place in a highly regioselective manner, 106 and the regioselectivity with 4,5-pyrimidyne 28 is also governed by the cumulenic structure (Scheme 22). 107,108 The regiochemical outcome of the reaction using various indolynes has been explained by difference in internal angles of the indolynes obtained from quantum chemical calculations, where flatter or more distorted end of the carbon-carbon triple bond of indolynes is apt to be coupled with nucleophile; 68,69 however, arguments based on the above electronic/steric effect lead to similar predictions (Scheme 23).…”
Section: Heteroarynesmentioning
confidence: 99%
“…[1,2] In recent years, studies on aryne-based reactions have achieved some remarkable success, particularly in sequential reactions with a nucleophile and an electrophile for the preparation of complex ortho-disubstituted arene derivatives, [3][4][5] which are difficult to synthesize by other methods. Most importantly, these advances have shown that the insertion of aryne compounds into various element-element s-bonds can be achieved even under transition-metal-free conditions.…”
mentioning
confidence: 99%